Indoor Beach Di Pekanbaru Dengan Penerapan Prinsip Desain Zaha Hadid - Inggit Duwi Saputra; Wahyu Hidayat; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pekanbaru citizen have a quite high interest in beach tourism. However needs of this community are not supported due to none of beach tourism in Pekanbaru. To reach the beach tourism thecommunity have to out of the town and moreover the atmospheres are bothered by unarranged area, colored water and muddy sand. The presence of Indoor Beach will become a solution for the needsof Pekanbaru citizen in beach tourism, which will provide a sense of comfort, secure and control all of the beach tourism activities. Existence of an artificial beach in Pekanbaru is quite rare. Thedesign of Indoor Beach using Zaha Hadid's design principles. Zaha Hadid is an architect whose known as unique building design so it will be in tune with the uniqueness of Indoor Beach. Zaha Hadid's design principles will be applied in the abstract formations, dynamic shapes, context to thesurrounding site, breaking and resistance and taking concepts from nature. The concept of Bono Waves is considered by the function of the building and the application of Zaha Hadid's designprinciples, and the concept will also be applied in the form of the process of the occurrence and philosophy of the seven ghost waves.Keyword: Indoor Beach, Zaha Hadid, Bono Waves